Impact of boron on Glycine max L. to mitigate salt stress by modulating the morpho-physiological and biochemical responses - Maira Tanveer; Athar Mahmood; Hussam F. Najeeb Alawadi; Atman Adiba; Muhammad Mansoor Javaid; Bilal Ahmad Khan; Abdul Wahid; Fnu Abdullah; Mahmoud F. Seleiman (BMC Plant Biology, 2025)
Abstract Background Boron (B) is an essential micronutrient in higher plants, contributing to various physiological processes. However, its protective mechanism in mitigating salt stress remained less understood. This study investigates that exogenous boron (0, 1, 2 kg ha− 1) can help alleviate salt stress (0, 60, 120 mM NaCl) in two soybean cultivars AARI-2021 (V1) and Ajmeri (V2). It examines B role in reactive oxygen species (ROS), secondary metabolites, and antioxidant defense systems in mitigating salt stress. Results Salt stress negatively impacted morph-physiological and biochemical attributes. Boron supplementation (2 kg ha− 1) reduced oxidative stress indicators, such as malondialdehyde (by 18% in V1 and by 21% in V2) and hydrogen peroxide (by 30% in V1 and by 38% in V2). Moreover, foliar application of boron (2 kg ha− 1) increased the catalase (CAT) (58% in V1 and 57% in V2), superoxide dismutase (SOD) (7% in V1 and 10% in V2), and peroxidase (POD) (42% in V1 and 32% in V2) activities under salt stress. Salt stress also led to an increase in Na+ and a decrease in K+ and Ca2+. However, boron supplementation enhanced K+ and Ca2+ in salt-stressed plants. Furthermore, boron application (2 kg ha− 1) increased the activity of secondary metabolites, total phenols content (TPC) (by 52% in V1 and by 59% in V2), total flavonoid content (TFC) (by 27% in V1 and by 21% in V2), and anthocyanins (ANTs) (by 33% in V1 and by 25% in V2) under salt stress. Conclusion This study suggests that B can reduce salinity-induced oxidative damage in soybean plants by modifying antioxidant defense and secondary metabolites and preserving ion homeostasis. Graphical abstract